The efficiency of linear Fresnel reflectors in producing superheated steam for power plant drive - Ghodbane Mokhtar (EDP Sciences, 2021)
Solar energy is one of the most important sources of renewable energies, which is widely used in many fields, such as electricity production through direct production of superheated steam based on Linear Fresnel Reflector. This study aims to show the optical and thermal behavior of linear Fresnel solar reflectors field directed to the electricity production in El-Oued region at Algeria. Four days of different weather data have been selected to track the change in solar field performance. Numerical optical modeling has shown that the optical performance of the solar field has reached 53.60 %, while the thermal study based on the numerical solution of the energy balance equations of the receiver tube proved that the thermal efficiency was 37.3 % and the average thermal loss coefficient was limited between 5.72 and 5.98 W/m²K. As for the superheated steam temperature, the lowest value was recorded in December with a value of 501 K. The results obtained are very compelling and encouraging to invest in this low-cost technology.